SEJARAH DAN TANTANGAN GEREJA KATOLIK DAYAK PERGUNUNGAN MERATUS - Adinugraha, Silvester (STP St. Bonaventura Medan, 2018)
Since 2008, the Banjarmasin Diocese Church has launched a mission for the Dayak people of the Meratus Mountains, called Miri Meratus. The birth of this mission marked the forerunner to the birth and development of the Catholic Church in the Meratus Mountains, South Kalimantan. Now that they are 10 years old, many things have changed and presented their own challenges. Encouraged to find out the situation of the Meratus Catholic Church from birth to the present, the author conducted field research, specifically at Stasi St. Paul Magalau. The results show that in terms of quality there is a graph of improvement every year, but in the context of church life, Stasi St. Paulus Magalau Catholic Church has not experienced significant development